2022
DOI: 10.1177/23743735221077527
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Stakeholders in the Development of a Reproductive Goals Decision AID for Women with Cystic Fibrosis

Abstract: Objective: More people with cystic fibrosis (pwCF) are reaching adulthood and considering their reproductive futures. Unfortunately, many pwCF report gaps in their reproductive healthcare. We describe measures of stakeholder engagement in developing a reproductive goals decision aid for women with CF called MyVoice:CF. Methods: Stakeholders reviewed the content, design, and usability of the tool, which was informed by prior research related to CF family planning experiences and preferences as well as a concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The relationship between the different ways and the providers (e.g., physician vs. other PwCF) involved in the information supply process and their integration seems to be fundamental to empower the subjects affected by CF in the decision‐making process: this involves the analysis of several characteristics both intrinsic and extrinsic, such as the risks for the mother and the child, the environmental support and the health status at the baseline. Our results are consistent with a recent research on the need for a decision support in relation to pregnancy for PwCF; for instance, Stransky et al (2022) have suggested a novel web‐based, patient‐centred reproductive goals decision aid for women with CF (called MyVoice:CF) to understanding options and a decreased decisional conflict regarding reproductive goals. For PwCF, coping with pregnancy is a challenging experience, where they have to mediate between the emotional response to needs, desires, expectations, concerns and feelings and the limitations imposed by the chronic health condition.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between the different ways and the providers (e.g., physician vs. other PwCF) involved in the information supply process and their integration seems to be fundamental to empower the subjects affected by CF in the decision‐making process: this involves the analysis of several characteristics both intrinsic and extrinsic, such as the risks for the mother and the child, the environmental support and the health status at the baseline. Our results are consistent with a recent research on the need for a decision support in relation to pregnancy for PwCF; for instance, Stransky et al (2022) have suggested a novel web‐based, patient‐centred reproductive goals decision aid for women with CF (called MyVoice:CF) to understanding options and a decreased decisional conflict regarding reproductive goals. For PwCF, coping with pregnancy is a challenging experience, where they have to mediate between the emotional response to needs, desires, expectations, concerns and feelings and the limitations imposed by the chronic health condition.…”
Section: Discussionsupporting
confidence: 92%
“…We developed two decisions aids (see Figure 4)-MyVoice:Rheum and MyVoice:CF-to help women (1) conceptualize the benefits and potential health risks of parenting, pregnancy, and/or pregnancy avoidance in the context of their conditions; (2) recognize and refine their reproductive goals; and (3) communicate these goals to their health care teams. Tool development centered on engagement with patients, clinicians, and reproductive health specialists to ensure that the content was accurate (Principle 1: Interdisciplinary stakeholder-inclusive teams), reflected patients' specific preferences and information priorities (Principle 2: Supporting a patient-centered approach), and helped to prepare patients for shared reproductive decision-making with clinicians in ways that enable them to receive the reproductive health care that meets their needs and preferences (Principle 3: Advancing reproductive health equity) [61,62]. Although the content of MyVoice:Rheum and MyVoice:CF is different and disease-specific, we developed the tools in tandem to maximize efficiencies related to time and expense.…”
Section: Tools To Address Considerations Related To Chronic Medical C...mentioning
confidence: 99%
“…Interventions to support people with cystic fibrosis achieve their reproductive goals can be focused on patient-facing, provider-facing, or systems-based change. Recently, a novel patient-facing, web-based reproductive decision support tool called MyVoice: CF to assist women with cystic fibrosis consider their reproductive futures and family planning needs was found to be highly acceptable, appropriate, and usable for a cystic fibrosis population [65,66]. Provider training in relationship-centered communication has also been found to be feasible for cystic fibrosis providers and may be adapted to improve family planning discussions [67].…”
Section: Parenthoodmentioning
confidence: 99%